1999
DOI: 10.1038/6360
|View full text |Cite|
|
Sign up to set email alerts
|

Neuronal growth cone collapse triggers lateral extensions along trailing axons

Abstract: Axonal outgrowth is generally thought to be controlled by direct interaction of the lead growth cone with guidance cues, and, in trailing axons, by fasciculation with pioneer fibers. Responses of axons and growth cones were examined as cultured retinal ganglion cell (RGC) axons encountered repellent cues. Either contact with cells expressing ephrins or mechanical probing increased the probability of lead growth cone retraction. Lateral extension of filopodia and lamellipodia hundreds of microns behind the lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 42 publications
(30 reference statements)
1
33
0
Order By: Relevance
“…Typically uncollapsed growth cones displayed the common ‘hand like’ morphology, and collapsed growth cones appeared as thin stumps. Growth cones were counted only at the end of neurites, even when significant growth cone-like processes were observed along the shaft of a neurite, as these lateral extensions can occur in response to the collapse of the leading growth cone [76]. Examples of collapsed versus uncollapsed growth cones are illustrated in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…Typically uncollapsed growth cones displayed the common ‘hand like’ morphology, and collapsed growth cones appeared as thin stumps. Growth cones were counted only at the end of neurites, even when significant growth cone-like processes were observed along the shaft of a neurite, as these lateral extensions can occur in response to the collapse of the leading growth cone [76]. Examples of collapsed versus uncollapsed growth cones are illustrated in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it is known that growth cones respond to increased NO by collapsing in a rapid and reversible manner (Hess et al, 1993;Renteria and Constantine-Paton, 1996), a process that may, in turn, stimulate back branching along the axon shaft (Davenport et al, 1999). Indeed, pauses in the forward extension of growth cones in vitro have been correlated with the later formation of interstitial branches (Szebenyi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…EphA3-Fc binds to ephrin A ligands to inhibit their function, and this interferes with temporal axon branching from retinal explants in a modified stripe assay (12). By using an RGC-tectal cell coculture system, Davenport et al (27) showed an intriguing phenomenon that sprouting of branches from trailing axons was induced several hundred micrometers behind the collapse site of leading axons by ephrin-A ligands. This sprouting might be a fundamental in vivo mechanism for topographically specific branching.…”
Section: Discussionmentioning
confidence: 99%
“…Graded ephrin-A5 expression stops growth cone advance on the surface of the posterior tectum. Based on in vitro studies, ephrin-A5 may also trigger the formation of secondary arbors along the primary axon that dive to the deeper tectal layers (27). These arbors define the retinotopic map in the SFGS where ephrin-A5 acts again to restrict the topographically correct positions that will then be later refined by activity-dependent processes.…”
Section: Discussionmentioning
confidence: 99%